Milestones and Timescale of Poststroke Recovery: A Cohort Study - Marianna Loi; Alberto Zaliani; Marta Abbamonte; Elena P. Ferrari; Roberto Maestri; Luigi Trojano; Pietro Balbi (Behavioural Neurology)
Background. Progressive increase of an aging population in Western countries will result in a growth of stroke prevalence. As many stroke survivors chronically show severe disability, increase in economic, social, and medical burden could be expected in the future. Objective and subjective measures of poststroke recovery are necessary to obtain predictive information, to improve the treatments, and to better allocate resources. Aim. To explore a measure of the temporal dimension of poststroke recovery, to search for predictive association with multiple clinical variables, and to improve tailoring of poststroke treatments. Method. In this observational monocentric cohort study, 176 poststroke inpatients at their first cerebrovascular event were consecutively enrolled. A novel measure based on the time needed to reach the main milestones of motor recovery was proposed. Moreover, two commonly used outcome measures, a measure of global functioning (Functional Independence Measure (FIM™)) and a measure of neurological poststroke deficit (Fugl-Meyer scale), were collected for the investigations of possible predictors. Results. The patients showed a substantial increase in Fugl-Meyer and FIM scores during the rehabilitative treatment. The acquisition of three milestones was significantly associated with female sex (autonomous standing), length of stay and Fugl-Meyer initial score (autonomous walking), and Fugl-Meyer initial score (functional arm). These findings provided quantitative data on motor milestone reacquisition in a sample of poststroke patients. It also demonstrated the value of the Fugl-Meyer score in predicting the acquisition of two motor milestones, relevant for daily life activities. Conclusion. Systematic recording of the timescale of poststroke recovery showed that motor milestone reacquisition happens, on average and when attainable, in less than 30 days in our sample of patients. The present study underscores the importance of the Fugl-Meyer score as a possible predictor for better improvement in reacquisition times of milestone functional recovery.